Planning for incapacity by people with bipolar disorder under the Mental Capacity Act 2005 - Bartlett, Peter; Mudigonda, Mohan; Chopra, Arun; Morriss, Richard K.; Jones, Steven (Taylor & Francis, 2016)
The Mental Capacity Act 2005 provided a variety of legal mechanisms for people to plan for periods of incapacity for decisions relating to personal care, medical treatment, and financial matters. Little research has however been done to determine the degree to which these are actually implemented, and the approach to such advance planning by service users and professionals. This paper looks at the use of advance planning by people with bipolar disorder, using qualitative and quantitative surveys both of people with bipolar disorder and psychiatrists. The study finds that the mechanisms are under-used in this group, despite official policy in support of them, largely because of a lack of knowledge about them among service users, and there is considerable confusion among service users and professionals alike as to how the mechanisms operate. Recording is at best inconsistent, raising questions as to whether the mechanisms will be followed.